Conductive filament evolution in HfO2 resistive RAM device during constant voltage stress. Issue 9 (August 2015) - Lorenzi, P.; Rao, R.; Irrera, F.
Abstract: The resistance evolution under constant voltage stress of the low resistive state and the high resistive state of HfO2 based RRAM cells is studied from an experimental and theoretical point of view. A filamentary model based on ions hopping and oxygen vacancies generation phenomena is used to interpret the behavior of the cells. The gap between the tip of the filament and the metal electrode is the parameter governing the device resistance. The current experiments are simulated in terms of the time evolution of the gap length during the electrical stress. The impact of the stress voltage amplitude and the parameter variability on the degradation dynamics is emphasized. Highlights: The resistance evolution under constant voltage stress of the low resistive state and the high resistive state of HfO2 based RRAM cells is studied from an experimental and theoretical point of view. A filamentary model based on ions hopping and oxygen vacancies generation phenomena is used to interpret the behavior of the cells. The gap between the tip of the filament and the metal electrode is the parameter governing the device resistance. The experiments are simulated in terms of the time evolution of the gap length during the electrical stress.